Bridging the gap: mediating role of organizational citizenship behavior in the relationship between job satisfaction, compensation, and work loyalty - Sari, Elvia Siskha; Lanin, Dasman; Frinaldi, Aldri (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This research is motivated by the low level of employee work loyalty. This research aims to analyze the influence of job satisfaction and compensation on employee work loyalty with organizational citizenship behaviour as an intervening variable in the Padang City Government. The population in this study were all employees in the Regional Government of Padang City, totaling 8522 employees. The sampling technique used a purposive sampling technique with a sample size of 99 respondents.The sampling technique used in this research used the Probability Sampling method with the proportional stratified random sampling technique. The data analysis technique in this research uses path analysis techniques. Based on the research results, the conclusions of this research can be described as follows: 1) Job satisfaction has a positive and significant effect on employee work loyalty. 2) Compensation has a positive and significant effect on employee work loyalty. 3) Organizational Citizenship Behaviour has a positive and significant effect on employee work loyalty. 4) Job satisfaction has a positive and significant effect on employee organizational citizenship behaviour. 5) Compensation has a positive and significant effect on the organizational citizenship behaviour of employees in the Padang City Government.